If there be dragons - Hooper, Kay (Bantam Books, 2008)
In the isolated sanctuary of her Montana ranch, no one could hurt Brooke Kennedy, whose gift had led her to build walls of ice around her heart. One person had stormed those barricades--her friend Pepper, who embraced the world and meddled in the lives of those she loved. Now Brooke needed help, and Pepper sent troubleshooter Cody Nash to melt the barriers Brooke had raised.